Effectiveness and Efficiency Analysis of Mucipal Tax Revenue and Its Contribution toward Locally Generated Revenue in Sidereng Rappang District - Sartina Sartina; Sanusi Fattah; Abdullah Sanusi (Magister Management, Hasanuddin University, 2021)
The purpose of this research is to analyze the effectiveness and efficiency of the municipal tax revenues and their contribution towards original local government revenue in Sidenreng Rappang district. The study applied the descriptive quantitative method. The data obtained from the municipal tax revenues district and the budget realization report of Sidenreng Rappang district from the period between 2014 and 2019. This research uses the method of effectiveness and efficiency ratio to calculate local tax, local tax realization, local tax fees, local tax target, and local tax contribution. The result in this research indicates that local tax revenues in Sidenreng Rappang district during the period of 2014 are already effective. The annual local tax revenues are very effective. Interestingly, the contribution of local taxes towards original local government revenue in Sidenreng Rappang district is found still very low.